Pengaruh Partisipasi dan Latar Belakang Eksekutif terhadap Keterlibatan Eksekutif dan Pengembangan Teknologi Informasi - Azis, Endang Siti Astuti (Jurnal Aplikasi Manajemen, 2009)
This research rebuffed by the role of information technology that was very vital in the organization that is supporting the organization operation, decision making managerial and the strategic advantage. While the development of information technology in the organization really was determined by the involvement and participation of the executives in the management activity of information technology. The form of the involvement and participation of executives, was reflected in their behavior in his perception in the executive, the internal condition for the organization and the environment hi-tech that formed their culture. So as the situation like this will give their perception towards the increase in the achievement of the organization. The aim of this research was to analyze the explain the influence of the executive's participation, the background of the executive, towards the involvement of the executive in the management of information technology, the development of information technology. This research was explanatory research, that explained relations between the research variable with the analysis unit of the manager's individual/the executive and the staff and or the numbering information specialist 135 people. The analysis statistic that was used to test the hypothesis was the structural equality model (structural equation model/SEM) results of the research showed that from all over the number of hypotheses (five) that was proposed by all of them was accepted with 5 direct relations routes, the significant relations route positive.